COMPARATIVE STUDY OF THE RELATIVE EFFICACY OF KUMKUMADI CREAMS (WITH VARIOUS WATER AND OIL PHASE) FOR THEIR VYANGAHAR EFFECT - Usha, *Sharma; Preeti, Singh; G.K, Saxena; Mohita, Bohra (International Journal of Ayurveda and Pharma Research, 2017)
The importance of beauty and personality is increasing now a day as it is a competitive era. Along with increased demand of beautification, the problems are also increasing which cause damage to beauty or personality due to changed life style and polluted atmosphere. Among the personality damaging disorder or dis-beautifying conditions, Vyanga is such a condition which affects the beauty as well as personality. Many people are suffering from Vyanga today, among them women are commonly found due to changes occurring during pregnancy and use of cosmetics supplements. Vyanga is a KshudraRoga (skin disorder) affecting the skin for which many internal medicine and external applications are suggested in texts. Local application is more useful in skin disorders as it directly act on lesion. In the context of Vyanga, Kumkumadi Taila has been strongly suggested as it directly acts on the site of lesion and all its contents possess coloring and depigmentation properties.Kumkumadi cream with different bases was given to total 38 patients registered divided in three groups for duration of one month. All the three creams were found significantly effective (p<0.01) on moisture content of skin, size of lesion, color of lesion, itching and burning sensation of lesion. Among three, Kumkumadi cream no.2 was found most effective with relief of 67.94% in treating disease Vyanga.